(untitled) (Bon Voyage, 2023)
This paper explores mainly three phases of displacement experienced by refugees in Habiburahaman’s book First, They Erased Our Name: A Rohingya Speaks and potential solutions to address the challenges they face. Deriving from Beverly Crawford’s concept that “refugees live three lives,” which has been quoted in the book written by Alan Gratz- Refugee, the paper examines the distinct experiences of refugees as they flee from their homeland, seek refuge in another place or country, and establish lives in foreign lands. Using the plight of Rohingya refugees in refugee camps as a reference point from the book, the paper argues that each phase of displacement dispenses with exclusive challenges and insecurities for refugees. The paper also discusses the role of theories in highlighting the problems and giving possible solutions to those complications of displacement. Additionally, the paper comprehends various insights from different philosophers and theorists on the topic of refugee displacement, providing a theoretical framework to address this global issue through a novel. Ultimately, the paper aims to offer a comprehensive understanding of the experiences of refugees in the book “...A Rohingya Speaks” and to propose possible implications to help refugees rebuild their lives after various phases of displacement.